Developing Lectora Based-Mind Mapping Interactive Media For Learning Arabic Nouns And Verbs/ ØªØ·ÙˆÙŠØ± ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„Ø¥Ø¹Ù„Ø§Ù… Ø§Ù„ØªÙØ§Ø¹Ù„ÙŠØ© Ø§Ù„Ù‚Ø§Ø¦Ù…Ø© Ø¹Ù„Ù‰ Ø§Ù„Ø®Ø±Ø§Ø¦Ø· Ø§Ù„Ø°Ù‡Ù†ÙŠØ© Ø§Ù„Ù…Ø³ØªÙ†Ø¯Ø© Ø¥Ù„Ù‰ Lectora Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ø£Ø³Ù…Ø§Ø¡ ÙˆØ§Ù„Ø£ÙØ¹Ø§Ù„ - Walimatul Fara, Elwin; Kholisin, Kholisin; Maziyah, Laily (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
This study aimed to produce a media named Lectora-based mind mapping interactive media for learning verbs and nouns. The research and development method used the Borg and Gall development model. The result is an interactive mind mapping media based on Lectora for learning verbs and nouns. The advantage of this media is that it can be used offline using a computer. However, it cannot be used with smartphones yet. Its use is easy because it is equipped with instructions, icons, and exciting animations. Students can access the first page of the application with the help of instructions and start the material by clicking the button of the desired material. Â They can use it independently without the presence of a teacher. As they can also choose the material they want without having to start from the beginning of the chapter. Based on the material expert trial results, the result was 65%, the media expert trial was 93%, the small group trial result was 95%, and the large group trial was 97%. It was concluded that an average of 87.5% was categorized as very valid and feasible to use as a learning medium.